PENGARUH MODEL GUIDED INQUIRY TERHADAP KETERAMPILAN METAKOGNITIF DAN HASIL BELAJAR SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Yuni Sarah Agustina Nababan; Makharany Dalimunthe (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to determine the effect of the guided inquiry model on metacognitive skills and student learning outcomes on electrolyte and non-electrolyte solution materials. Data analysis used the N-Gain test, hypothesis prerequisite tests (homogeneity test and normality test), and hypothesis tests (independent t-test and correlation test). N-Gain learning outcomes in the experimental class were 0.785 higher than the control class of 0.587. The results of the t-test for the first hypothesis showed a calculated t value of 4.695 while for the t-table it was 1.999, because the calculated t value> t-table then there was an influence of the learning model on metacognitive skills, then on the learning outcomes the calculated t value was 6.939, while the t-table value was 1.999, because the calculated t value> t-table then there was an influence of the learning model on learning outcomes, this means that H0 was rejected and Ha was accepted. The correlation test of the calculated r value (Pearsen correlation) is 0.586 while for the table r it is 0.349 because, calculated r > table r then there is a relationship between the two variables. It can be concluded that the Guided Inquiry model has a significant effect on metacognitive skills and student learning outcomes, and there is a correlation between the two in class X of Budi Satrya Private High School. Keyword: Guided Inquiry Model, Metacognitive Skills, Learning Outcomes Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model guided inquiry terhadap keterampilan metakognitif dan hasil belajar siswa pada materi larutan elektrolit dan non elektrolit. Analisis data menggunakan uji N-Gain, uji prasyarat hipotesis (uji homogenitas dan uji normalitas), dan uji hipotesis (uji t independen dan uji korelasi). N-Gain hasil belajar pada kelas eksperimen 0,785 lebih tinggi dibanding kontrol 0,587. Hasil uji t untuk hipotesis pertama menunjukkan nilai t hitung sebesar 4,695 sedangkan untuk t tabelnya adalah 1,999, karena t hitung > t tabel maka terdapat pengaruh model pembelajaran terhadap keterampilan metakognitif, kemudian pada hasil belajar nilai t hitung sebesar 6,939, sedangkan nilai t tabelnya sebesar 1,999, karena t hitung > t tabel maka terdapat pengaruh model pembelajaran terhadap hasil belajar, hal tersebut berarti H0 ditolak dan Ha diterima. Uji korelasi nilai r hitung (pearsen correlation) sebesar 0,586 sedangkan untuk r tabelnya sebesar 0,349 karena, r hitung > r tabel maka terdapat hubungan antar dua variabel. Dapat disimpulkan bahwa model Guided Inquiry berpengaruh signifikan terhadap keterampilan metakognitif dan hasil belajar siswa, serta terdapat korelasi antara keduanya di kelas X SMA Swasta Budi Satrya. Kata kunci: Model Guided Induiry, Keterampilan Metakognif, Hasil Belajar